Model wczesnego ostrzegania jako narzędzie oceny kondycji finansowej spółek hodowli roślin i zwierząt - Grzegorzewska, Emilia (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The objective of the study was to assess the financial condition of a selected group of agricultural enterprises by the early warning model, which takes into account the specify of the agricultural sector. The study examines plant and animal for this study breeding companies owned by Agricultural Property Agency were selected. The analysis covered the years 2008–2010. The results showed that the end of the period, almost half surveyed companies were in poor financial condition. The biggest financial risk was noted in the companies of horse breeding. In 2010 almost two third of the companies obtained a value of early warning model substantially below the border point. The best financial condition was characterised by the company’s animal husbandry. The average index value YSHO during the period was above 4.0. Carried out the analysis indicated agricultural enterprises located in the best and the weakest financial condition. Companies in which the indicator YSHO signals financial risk should undergo a thorough ratio analysis to identify the critical areas of activity and determine the corrective action.